Anti‐VEGF antibody therapy induces tumor hypoxia and stanniocalcin 2 expression and potentiates growth of human colon cancer xenografts. Issue 2 (6th January 2014) - Miyazaki, Shinichiro; Kikuchi, Hirotoshi; Iino, Ichirota; Uehara, Takashi; Setoguchi, Tomohiko; Fujita, Takeshi; Hiramatsu, Yoshihiro; Ohta, Manabu; Kamiya, Kinji; Kitagawa, Kyoko; Kitagawa, Masatoshi; Baba, Satoshi; et al.
<x xml:space="preserve">Abstract</x> Tumor angiogenesis plays a critical role in colorectal cancer progression. Recent randomized clinical trials have revealed the additive effect of bevacizumab, a humanized monoclonal antibody against vascular endothelial growth factor (VEGF)‐A, to conventional chemotherapy in the improved survival of patients with metastatic colorectal cancer. However, a number of preclinical reports indicate the development of resistance to anti‐angiogenic therapy. In this study, we addressed the effects of anti‐VEGF antibodies on the growth and malignant behavior of colorectal cancer cells. TK‐4, a solid tumor strain derived from a colon cancer patient, was subcutaneously or orthotopically implanted into nude mice. Short‐term administration of anti‐VEGF antibodies inhibited the growth of cecal tumors at day 14 by suppressing mitosis, but prolonged treatment resulted in the recovery of cellular proliferation and suppression of apoptosis at day 35. Intratumoral hypoxia induced by anti‐VEGF antibody treatment resulted in activation of hypoxia inducible factor‐1α protein and an increased number of aldehyde dehydrogenase 1‐positive tumor cells. In microarray analysis, stanniocalcin 2 (STC2) was the most highly upregulated gene in anti‐VEGF antibody‐treated tumors. In vitro analyses showed that the growth and migration of SW480 colon cancer cells under hypoxic conditions were significantly inhibited by knockdown of STC2. In vivo serial transplantation of TK‐4 revealed that long‐term administration of anti‐VEGF antibodies increased the tumorigenicity of colon cancers and accelerated tumor growth when transplanted into secondary recipient mice. Our data provide a potential molecular explanation for the limited clinical effectiveness of anti‐VEGF antibodies.